Heart transplantation in an infant with Williams‐Beuren syndrome and rapidly progressive ischemic cardiomyopathy. (29th February 2020) - Baez Hernandez, Nathanya; Kirk, Richard; Davies, Ryan; Roumillat, Jessica; Sutcliffe, David; Bano, Maria; Butts, Ryan
Abstract: Ischemic cardiomyopathy with resultant refractory HF may occur in patients with WBS, often as the result of coronary involvement with SVAS. The rapid development of arteriopathy at a young age raises concerns regarding transplant candidacy due to progressive stenoses at other arterial sites with potential detrimental impact on long‐term heart graft function. We report a 2‐month‐old male infant diagnosed with mild aortic stenosis during the neonatal period, but subsequently developed rapidly progressive supravalvar and coronary artery stenoses leading to cardiogenic shock due to myocardial ischemia. The presentation led to the diagnosis of WBS. He required prolonged CPR including ECMO therapy. He subsequently underwent LVAD implantation as bridge to transplant and 4 days later heart transplantation. His post‐operative course was complicated by prolonged mechanical ventilation and extended intensive care unit and hospital stays. However, at follow‐up 18 months post‐transplant he continues to have normal graft function with mild, non‐progressive residual coarctation of aorta and non‐progressive moderately hypoplastic pulmonary arteries.